Kenya : Poverty Reduction Strategy Annual Progress Report; 2004/2005. (IMF Staff Country Reports; Country Report ;, 2007)
This paper examines Kenya's Poverty Reduction Strategy annual progress report. The Investment Program for the Economic Recovery Strategy is Kenya's medium-term strategy to foster economic growth and reduce poverty. Poverty is defined as the inability to command resources and is a multidimensional phenomenon, a characteristic that makes those afflicted face multiple deprivations owing to interactions of economic, political, and social processes. The government envisages strengthening the macroeconomic framework, a more responsible fiscal policy stance, and the unleashing of private sector participation and investment.